How Geography Makes Democracy Work - Carney, Richard W. (2016)
Why are some countries more democratic than others? Two dominant approaches characterize how scholars have answered this question: economic development or modernization theory and the vibrancy of civil society. But these explanations often face the critique of endogeneity, and have difficulty accounting for countries that are wealthy yet are nondemocratic (e.g., Brunei and Kuwait), or exhibit strong civil societies without corresponding democratic institutions (e.g., Bangladesh and Morocco). This paper offers a different approach. It argues that a country’s geographical attributes underlie and influence both economic development and civil society, and in turn affect democratic outcomes. Statistical evidence from over 100 countries offers evidence consistent with the argument. Case studies on twelfth century Italy, modern Malaysia, Malawi, and Paraguay illustrate the mechanisms at work.